Alterations in energy balance and the antioxidant system due to heat stress: focus on animal production - Montesinos-Cruz, Veronica; Parra Forero, Lyda Yuliana; García Contreras, Adelfa del Carmen (Frontiers in Animal Science, 2023)
In areas where the ambient temperature is above the thermoneutral zone, the economic loss from animals for human consumption, such as pigs, is worrying. Heat Stress (HS) increases body temperature and causes a subsequent reduction in feed intake. This reduction results in the loss of essential nutrients, such as amino acids, which are crucial for growth rate and the activation of vital biochemical mechanisms. However, the effects of HS on reactive oxygen species (ROS) generation, and the activation of mechanisms such as the antioxidant system associated with nuclear factor erythroid-derived 2-like-2 (Nrf2), energy balance, protein synthesis and mitochondrial biogenesis have received limited attention. In this work, we provide a comprehensive review of the existing evidence regarding the significance of nutritional components and their association with HS. We particularly emphasize ROS generation, mitochondrial alterations, and the activation of Nrf2, AMPactivated protein kinase (AMPK), and mammalian target of rapamycin (mTOR) signaling pathways in response to the disruption of homeostasis.